Groundwater rebound and seepage characteristics and water quality evolution in a sealed mining area in North China type coalfield - Huiyong YIN; Dehui SUN; Fangying DONG; Fanhua WANG; Lifeng ZHANG; Tao WU; Chao LIU; Yifan ZENG (Meitian dizhi yu kantan)
BackgroundThe seepage field and water quality evolution associated with the groundwater rebound induced by the sealing of mining areas significantly affects the prevention and control of mine water hazards, as well as the recycling of water resources. Systematically elucidating the mechanisms underlying the seepage-hydrochemistry synergy of groundwater is recognized as a fundamental scientific issue for promoting the collaborative management and resource development of the water systems in mining areas. MethodsBased on the engineering background of the sealed No.116 mining area in the Binhu Coal Mine, Zaozhuang, Shandong Province, this study investigated the groundwater rebound and seepage characteristics, along with the associated evolutionary patterns of ion concentrations and mineral phases in groundwater, using hydrochemical tests, numerical simulation, and theoretical calculation. Furthermore, this study characterized groundwater rebound and hydrochemical evolutionary models. Results and Conclusions The existing accumulated water was primarily distributed in the western part of the No.116 mining area in the Binhu Coal Mine. Based on the water inflow before the sealing of the mining area, it can be estimated that the accumulated water would fill the whole goaf within 426 days. Specifically, within the initial 90 days after sealing, the water inrush points continuously discharged water, causing the groundwater level in the goaf to rise to −450 to −250 m rapidly. Within 90‒360 days post-sealing, the groundwater rebound in the goaf slowed down, with the water level on both sides of the goaf reaching −150 m. Consequently, the water level remained relatively stable until at day 455 post-sealing, when the goaf was full of accumulated water. The process was largely consistent with the expected results. By this time, the groundwater flow field roughly reached equilibrium. During the water rebound along fractures and water inrush from Ordovician limestone and the fourteenth limestone aquifers, cation exchange was accelerated, with the Na+ and K+ concentrations increasing rapidly and the Ca2+ and Mg2+ concentrations decreasing significantly. At this stage, the quantities of mineral phases such as albite, potassium feldspar, and halite increased, while those of quartz, calcite, and dolomite decreased due to dissolution or precipitation. After the goaf sealing, water-rock interactions persisted during the reinjection of the accumulated water, but the cation exchange rate slowed down. The mineral phases showed similar but weakened variation trends compared to the water inrush stage. Finally, a hydrochemical equilibrium system characterized by high Na+/K+ and low Ca2+/Mg2+ concentrations was formed. The whole process reflects the hydrochemical evolution model of the sealed mining area from dynamic water inrush disturbance to slow self-equilibrium. The results of this study provide a reference for revealing the evolutionary pattern of the water environment in goaves under similar settings and offer a theoretical basis for the development and utilization of groundwater resources in sealed mines.